Tingkat Efisiensi Jerami Padi terhadap Kelangsungan Hidup Lobster Air Tawar (Cherax Quadricarinatus) pada Proses Transportasi Sistem Kering Selama 24 Jam - Fajar Purnomo; Muawanah Muawanah; Sasanti Sih Subekti (Journal on Education, 2022)
Dry system transportation using the principle of hibernation aims to suppress the metabolic processes of an organism so that in minimum environmental conditions the organism can survive. The survival of freshwater crayfish during transportation using the dry system is strongly influenced by the position of the lobsters in the packaging and the temperature of the media. This study examines the effectiveness of rice straw media in the transportation of crayfish with a comparison medium consisting of sponges and sawdust which are commonly used in the process of transporting crayfish. Research results on the survival rate of freshwater crayfish using rice straw media provide the most efficient survival results among other media. The process of transportation with different media had a very good survival impact on crayfish starting from treatment A using (sponge) with an average survival rate of 16.7 heads or (83.5%) of 20 heads. Treatment B used (wood powder) with an average survival rate of 17 or (85%) of 20 individuals. Treatment C used rice straw with an average survival rate of 18.3 individuals or (91.5%) of 20 individuals. The conclusion in this study is that the survival of freshwater crayfish using rice straw media provides the most efficient survival results among other media